La política de los intersticios: «De liberalitate et parsimonia» en El príncipe, de Nicolás Maquiavelo - Gaune, Rafael (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
This article proposes an annotated review of «De liberalitate et parsimonia», chapter XVI of Nicholas Macchiavello’s The Prince. It addresses how the Florentine author exposes the exceptionalities of misery and liberality as a mechanism of adaptation and interpretation of political reality. Both misery and liberality are part of a schema that expresses the nuances, exceptions, and twilights of real politics as well as the limits of human virtues.Also, this article dialogues with other Macchiavello’s texts (letters and Discorsi) and other chapters of The Prince.

El artículo propone una lectura comentada del capítulo XVI de El príncipe de Nicolás Maquiavelo, titulado «De liberalitate et parsimonia». Se abordarán las excepcionalidades de la miseria y la liberalidad expuestas por el florentino como parte de un mecanismo de adaptación y lectura de la realidad política. Tanto la miseria como la liberalidad son parte de un esquema que expresa los matices, las excepciones y los claroscuros de la política real, así como los límites de las virtudes humanas. Del mismo modo, se dialoga con otros textos de Maquiavelo (cartas y Discorsi), así como con capítulos centrales de El príncipe.
The Politics of Interstices: «De Liberalitate et Parismonia» in Nicholas Macchiavello’s The Prince
Keywords: Maquiavelo; El príncipe (capítulo XVI); Miseria; Liberalidad; https://purl.org/pe-repo/ocde/ford#5.05.00